Comparative study of feline arterial thromboembolism treated with the combination of atenolol-clopidogrel and single clopidogrel - Lady Konfidenia Chintari (ARSHI Veterinary Letters, 2022)
Feline Arterial Thromboembolism (FATE) is one of the most devastating consequences of cardiac disease in cats, characterized by a thrombosis that leads to an obstruction in the blood vessel. This disease predominantly occurs with Hypertrophic Cardiomyopathy (HCM) condition. The purpose of this case study is to corroborate the comparison of therapy between two FATE cases treated with a combination of atenolol and clopidogrel compared to clopidogrel only. Two cats were brought by the owner to the clinic with the same conditions including paraparesis, hypothermia, and pale hind paws. Physical examination revealed that both cats got hypothermic, had no femoral pulse, and pale hind legs. The blood test result showed an increase in lactate from the femoral vein and hyperkalemia in the body. Echocardiographic found HCM characterized by thickening of the left ventricular posterior wall and interventricular septum. The first cat was given the combination of atenolol (beta-blocker) and clopidogrel (antiplatelet), with supportive medications such as analgesic, omega 3, and diuretic. On the other hand, the second cat was given the same exact medications, but without atenolol (beta-blocker). After 9 days of treatment and hospitalization, the first cat that was administered a combination of atenolol and clopidogrel died after got hypotension and dyspnea. While the second cat that was given single clopidogrel survived with good clinical conditions and recovered from the lameness